Expression of core 3 synthase in human pancreatic cancer cells suppresses tumor growth and metastasis. Issue 12 (5th August 2013) - Radhakrishnan, Prakash; Grandgenett, Paul M.; Mohr, Ashley M.; Bunt, Stephanie K.; Yu, Fang; Chowdhury, Sanjib; Hollingsworth, Michael A.
<x xml:space="preserve">Abstract</x> Core 3‐derived glycans, a major type of O‐glycan expressed by normal epithelial cells of the gastrointestinal tract, are downregulated during malignancy because of loss of expression of functional β3‐N‐acetylglucosaminyltransferase‐6 (core 3 synthase). We investigated the expression of core 3 synthase in normal pancreas and pancreatic cancer and evaluated the biological effects of re‐expressing core 3 synthase in pancreatic cancer cells that had lost expression. We determined that pancreatic tumors and tumor cell lines have lost expression of core 3 synthase. Therefore, we re‐expressed core 3 synthase in human pancreatic cancer cells (Capan‐2 and FG) to investigate the contribution of core 3 glycans to malignant progression. Pancreatic cancer cells expressing core 3 synthase showed reduced in vitro cell proliferation, migration and invasion compared to vector control cells. Expression of core 3 O‐glycans induced altered expression of β1 integrin, decreased activation of focal adhesion kinase, led to the downregulation of expression of several genes including REG1α and FGFR3 and altered lamellipodia formation. The addition of a GlcNAc residue by core 3 synthase leads to the extension of the tumor‐associated Tn structure on MUC1. Orthotopic injection of FG cells expressing core 3 synthase into the pancreas of nude mice produced significantly smaller tumors and decreased metastasis to the surrounding tissues compared to vector control FG cells. These findings indicate that expression of core 3‐derived O‐glycans in pancreatic cancer cells suppresses tumor growth and metastasis through modulation of glycosylation of mucins and other cell surface and extracellular matrix proteins.